Towards an objective account of nutrition and health in colonial Kenya - Moradi, A (2008)
How well did Kenyans do under colonial rule? It is common sense that Kenyans suffered under exploitative colonial policies. The overall impact, however, is uncertain. This study presents fresh evidence on nutrition and health in colonial Kenya by (1) using a new and comprehensive data set of African army recruits and civilians and (2) applying a powerful measure of nutritional status: mean population height. Findings demonstrate huge regional inequalities but only minor changes in the mean height of cohorts born 20 years before and after colonisation. From 1920 onwards secular improvements took place which continued after Independence. It can be concluded that however bad colonial policies and devastating short term crises were, the net outcome of colonial times was a significant progress in nutrition and health.